2018
DOI: 10.1038/s41598-018-28785-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and hepatoprotective effects of exopolysaccharides isolated from Pleurotus geesteranus on alcohol-induced liver injury

Abstract: The present work investigated the hepatoprotective role of exopolysaccharides (EPS) isolated from the mushroom Pleurotus geesteranus with respect to alcohol-induced liver injury in mice. Based on a physico-chemical analysis, the EPS produced by Pleurotus geesteranus was identified as a heteropolysaccharide with α-glycosidic bond. The results revealed that prophylactic application of the EPS reduces detrimental alcoholic effects on the liver. This observation was followed by decreased levels of total cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…The secretion of TNF and IL-12 by PCPS-activated DCs could significantly be eased by an anti-Dectin-1 antibody, as well as by a Syk kinase and a Raf-1 inhibitor, suggesting that PCPS motivated Dectin-1 signaling at least partly via the Syk- and the Raf1-dependent pathways in DCs [ 85 ]. Song et al reported that anti-inflammatory and hepatoprotective effects of exopolysaccharides (EPS) extracted and purified from Pleurotus geesteranus on alcohol-induced liver injury [ 210 ]. Changes in anti-inflammatory factors are essentially consistent with the other EMFs polysaccharides mentioned above.…”
Section: Antiviral Mechanisms Of Emfs Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The secretion of TNF and IL-12 by PCPS-activated DCs could significantly be eased by an anti-Dectin-1 antibody, as well as by a Syk kinase and a Raf-1 inhibitor, suggesting that PCPS motivated Dectin-1 signaling at least partly via the Syk- and the Raf1-dependent pathways in DCs [ 85 ]. Song et al reported that anti-inflammatory and hepatoprotective effects of exopolysaccharides (EPS) extracted and purified from Pleurotus geesteranus on alcohol-induced liver injury [ 210 ]. Changes in anti-inflammatory factors are essentially consistent with the other EMFs polysaccharides mentioned above.…”
Section: Antiviral Mechanisms Of Emfs Polysaccharidesmentioning
confidence: 99%
“…Changes in anti-inflammatory factors are essentially consistent with the other EMFs polysaccharides mentioned above. [ 210 ].…”
Section: Antiviral Mechanisms Of Emfs Polysaccharidesmentioning
confidence: 99%
“…The DFG was purified by DEAE‐52 cellulose column chromatography according to the method of Song et al (2018) with a slight modification. A 1 ml of the DFG rough solution obtained by previous step was diluted into 5 ml and was fractionated by the DEAE‐52 cellulose column (26 mm × 400 mm); the column was stepwise eluted with distilled water and 0.2 mol/L NaCl solution with a flow rate of 1.0 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…Magnolol Down-Regulated the Expression of iNOS, Cox-2, and CYP2E1 in Alcoholic Liver Damage iNOS and Cox-2 are usually activated in the process of oxidative stress and inflammation, which result in tissue damage (Song et al, 2018). CYP2E1 is also a key enzyme in regulating alcoholic liver damage.…”
Section: Magnolol Increased the Antioxidant Enzymes Of Sod And Gsh-pxmentioning
confidence: 99%